Comparative life cycle assessment of standard, cellulose-reinforced and end of life tires fiber-reinforced hot mix asphalt mixtures. (1st March 2020) - Landi, Daniele; Marconi, Marco; Bocci, Edoardo; Germani, Michele
Abstract: A change in the current waste management practices is needed to improve the reuse and recycling rates and limit the increasing environmental impacts (EI) on the environment. The construction sector is one of the major contributors to the global EI, regarding energy consumption, emissions released into the atmosphere and extracted natural resources. In this context, the reuse of waste and scraps from other sectors/production chains (i.e. fibers from end of life tires – ELT) in road pavements potentially represents a best practice. This study presents a comparative life cycle assessment (LCA) among three different typologies of hot mix asphalt mixtures (HMA): standard, cellulose-reinforced and ELT fiber-reinforced. The study focuses on the environmental analysis of the realization and maintenance of 1 m 2 of HMA mixtures for a motorway road, during a time lapse of 30 years. The life cycle inventory includes primary data, collected from different industrial companies and from laboratory test, secondary data, derived from the GaBi professional database 2016. The service lives of the different typologies of HMA have been evaluated through a laboratory study and a full-scale application in a trial section located in an important Italian motorway. The porous asphalt mixture containing ELT fibers showed about 70% increase in the fatigue resistance with respect to the porous asphalt mixture containing cellulose fibers. The environmental impacts have been quantified in terms of Cumulative Energy Demand (CED), Global Warming Potential (GWP), and ReCiPe midpoint and endpoint indicators. The obtained results show that raw materials (particularly bitumen) are the most impactful flows for all the three considered mixtures and for all the impact categories. Also the transportation phases contribute with relevant impacts, while energy flows consumed during the HMA preparation and laying are almost negligible. Considering the CED, GWP and ReCiPe endpoint indicators, the ELT fiber-reinforced HMA resulted the best alternative (reduction of 25% in comparison with the standard HMA), followed by the cellulose-reinforced HMA (−10%), thanks to the higher service life. For some ReCiPe midpoint categories (Agricultural land occupation, Freshwater ecotoxicity, Freshwater eutrophication, Marine eutrophication and Terrestrial ecotoxicity), instead, the worst scenario is the cellulose HMA, due to the high contribution of the cellulose material.